Sustainability, Climate Change and the Green Economy - Nhamo, Godwell; Nhamo, Godwell; Mjimba, Vuyo (Africa Institute of South Africa, 2016)
Written by 18 authors, this book on Sustainability, Climate Change and the Green Economy brings together insights at the nexus of the four key concepts embedded in its title. The book is unpacked in six parts. Part 1 is a single chapter that covers the context of the topic. Part 2 looks at the green economy and green jobs, and addresses the challenges of government coordination and socio-economic development, with emphasis on skills and immigration regimes. Part 3 reflects on sustainable development, with a focus on relearning our wants and needs, and provides critical reflection on engineering for sustainable development. Management of natural resources and wetlands makes up Part 4, which teases out issues on timber harvesting, as well as challenges and opportunities in addressing environment-economic development and growth conflicts. A critique of climate change coverage in news media, mainstreaming climate change into wildlife policies, and tourism, are matters covered in Part 5. The last part (Part 6) is another single chapter, which articulates emerging issues from the whole book and presents some policy and take-home messages. Given the growing literature in the field of sustainability, climate change and the green economy, this piece will prove a must-read for policy makers, academics, industry and civil society.